Perbandingan Kedalaman Pengikisan Logam Dalam Larutan Feri Klorida - Sri Nengsih (PTE FTK UIN Ar-Raniry, 2021)
A comparative study of metal removal in ferric chloride solution has been completed. The purpose of this study is the effect of acid solution cause material removal of various types of metals such as steel, iron, aluminum and tin. Previously this plate had been prepared by determine the dimensions of the plate size, plate mass and ensuring the plate surface is flat. After that, the plates were immersed in ferric chloride solution with a solution percentage of 27% gram / ml in water for 2 hours. Metal plates had been cleaned and dried and then carried out post-immersion measurements for plate mass, plate dimensions, solution temperature and the acidity of the solution. The result of measurement show the metal plates of steel, iron, aluminum and tin have removed material with a depth of 0.350 mm; 0.550 mm; 0.5625 mm and 0.665 mm. The mass lost after immersion in ferric chloride solution was 2.2 g; 3.9 g; 3.6 g and 7.6 g. Through Faraday's Law, it has been found that the calculation of the material removal rate (MRR) is 0.140 cm3/hour; 0.252 cm3/hour; 0.667 cm3/hour and 0.659 cm3/hour. This has shown the acid solution can remove the metal surface,when the density of the metal is large, material removal rate is low. Therefore, further studies are needed to observe the presence of impurities in the plate and the surface roughness of the metal plate after immersion.